Denmark : Report on Observance of Standards and Codes (ROSC). (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses findings of the Report on Observance of Standards and codes for Denmark. Denmark has a high level of compliance with the Basel Core Principles for Effective Banking Supervision. The Danish Financial Supervisory Authority (DFSA) has the appropriate legal authority to carry out supervision effectively, and its risk based approach has focused well on the key elements of risk within its banking system. Its powers and supervisory approach have evolved significantly since the recent global crisis, and the DFSA emerged as a proactive supervisor. Its overall supervisory approach is sound, and the compliance with the credit-risk and capital adequacy related principles is uniformly high.